CLEFT PALATE IN A LAMB - A CASE REPROT - Veeraiah, G; Srinivas , Manda; Rani , N Lakshmi (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The present communication reports the clinical findings and necropsy in a case of congenital cleft palate in a lamb.